The Effect of Thin-Layer Elements in Structural Modeling of Rail-Track Supporting System - Yeat, Chooi Fong (2006)
A conventional track system consists of rails, sleepers, ballast, sub-ballast and sub-grade. A track foundation on the basis of live load response and permanent settlement, it is necessary to use an analytical model that will realistically represent the actual behaviour of this track system subjected to actual load. This study deals with the development of numerical modeling of Malaysian railway track along with the supporting system. The model is capable to simulate the sleeper, ballast, sub-ballast, soil layers and their interaction as a single compatible unit. Under plane strain condition, the coupled finite-infinite elements were implemented to represent the near field and far field behaviour of media. Thin-layer elements have been used to represent the interfacial behaviour between sleepers and ballast. The following constitutive relationships were adopted in this study: (i)-Linear Elastic (ii)-Elasto-plastic